DERBY: WA FOOTY FANS ON THE GAME'S GREATEST RIVALRY - Whish-Wilson, David; Gorman, Sean (2017)
'THE STATE IS DIVIDES, IT'S NOT LIFE OR DEATH, IT'S MORE IMPORTANT! So says a poster on Dennis Cometti's wall - and that's just what David Whish-Wilson and Sean Gorman found out when they interviewed 36 fans of the WEST COAST EAGLES and the FREMANTLE DOCKERS, including DAVID WIRRPANDA . SHAUN McMANUS . DENNIS LILLEE . MELISSA PARKE . ROSS McLEAN . LUC LONGLEY . ALISON FAN . JULIE BISHOP . JUSIN LANGER . GILLIAN O'SHAUGHNESSY and more!